CHANGES IN PRESCHOOL EDUCATION SYSTEM IN UZBEKISTAN - Nabieva Nazira Ismailovna (Research Parks Publishers, 2020)
The article summarizes the changes in the preschool education system in Uzbekistan, reforms and the content of decrees and decrees. The materials on the material and technical base of the preschool education system, educational and methodological developments, literature and the level of staffing were also analyzed.